Impact of previous macrolide use on invasive pneumococcal disease due to erythromycin-resistant serotypes in adults over 59 years of age - Fernández Chávez, Abelardo; García Comas, Luis; Manzano Espinosa, Luis; Yuste Lobo, Jose; Corral, Octavio Jorge; Aranaz Andrés, Jesús María (European Journal of Clinical Microbiology and Infectious Diseases, 2023)
The major goals of the study were to describe the invasive pneumococcal disease (IPD) cases due to erythromycin-resistant serotypes and to evaluate the association between these cases and recent macrolide use in individuals aged over 59 years. We selected cases of IPD reported between 2007 and 2016 in persons aged over 59 years living in the Community of Madrid (CM). We followed the European Committee on Antimicrobial Susceptibility Testing (EUCAST). The explanatory variables (age, sex, year of onset of symptoms, clinical presentation, serotypes, vaccination status) were taken from the Mandatory Notification System for Infectious Diseases System and from the Vaccination Information System. The cases were classified as either included in the 13-valent pneumococcal conjugate vaccine (PCV13) or not (nonPCV13). Associations between cases due to erythromycin-resistant serotypes and previous macrolide use (total, long and short-term) were adjusted with a logistic regression multivariate analysis. A total of 1,831 cases were identified, of whom 408 were erythromycin-resistant serotypes. PCV13 cases were associated with previous macrolide use (OR: 5.07), particularly long-acting types (OR: 8.61). NonPCV13 cases were associated with the use of total macrolides (OR: 3.48) and long-acting macrolides (OR: 4.26) suggesting that PCV13 did not reduce the IPD cases in patients with previous use of macrolides. Our results confirmed that previous macrolide consumption was associated with the presence of IPD due to erythromycin-resistant serotypes. The risk was higher with the use of long-term macrolides.
Keywords: invasive pneumococcal disease; pneumococcal conjugate vaccines; reduced antibiotic susceptibility; JCR